Peningkatan Digital Literasi Terhadap Ujaran Kebencian di Media Sosial Melalui Program “Room of Law” Bagi Siswa Sekolah Menengah Atas di Kota Serang - Fuqoha Fuqoha; Ananda Putri Anggraini; Nabila Dea Apipah (Pusat Studi Sosial dan Pengabdian Masyarakat Fisipkum Universitas Serang Raya, 2019)
The purpose of this community service activity is to provide education and understanding to students and the school towards the potential and dangers of hate speech through social media. It is hoped that through this activity encourage school students to avoid and combat the behavior of speech utterances especially on social media. The activity method is Participatory Learning and Action which emphasizes socialization, discussion and training and digital literacy education. The results of the “Room of Law” activities in this service show that students' knowledge is still weak about the utterances of hate in social media and the threat of punishment resulting from acts of hate speech. This service is still being carried out to create Agent of Against Hate Speech through training and education for Training of Train students.